Evaluation of CGIAR Excellence in Breeding Platform - McHugh, Karen; Morgan, Vanda; Ragot, Michel; Acharjee, Sumita; Noma, Freddy (CGIAR Independent Advisory and Evaluation Service, 2022)
The Evaluation of CGIAR Excellence in Breeding Platform (EiB) responds to the request of the System Council (the 2022-24 multi-year evaluation plan) to provide CGIAR with evaluative evidence for accountability and learning. The evaluation and its validation were conducted between August 2021 and April 2022; it is the first evaluation delivered since the approval of the CGIAR Evaluation Framework and Policy (2022).